2010
DOI: 10.1016/j.anbehav.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts induce affiliative interactions among bystanders in a tolerant species of macaque (Macaca tonkeana)

Abstract: Keywords: aggression appeasement Macaca tonkeana polyadic interaction primate social tension Tonkean macaque Aggression is potentially disruptive for social groups. Although individuals witnessing a conflict are not directly threatened by aggressive interactions, the aftermath of aggression appears to be a period of social instability. We expected bystanders to respond to conflicts by affiliating with other group members and so reducing social tension. To test this hypothesis we collected data on two captive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…To assess dominance relationships we built a matrix of supplantations. We then used MatMan version 1.0 (Noldus Information Technology, Wageningen, The Netherlands) to rank individuals in a dominance hierarchy (De Marco et al 2010).…”
Section: Observational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess dominance relationships we built a matrix of supplantations. We then used MatMan version 1.0 (Noldus Information Technology, Wageningen, The Netherlands) to rank individuals in a dominance hierarchy (De Marco et al 2010).…”
Section: Observational Methodsmentioning
confidence: 99%
“…The majority of researchers have focused on the behavior of sexual partners and competitors, and little is known about their influence on group-mates. Recent studies have shown that the outburst of conflicts influences the behavior not only of opponents but also of uninvolved individuals; in hamadryas baboons (Papio hamadryas hamadryas) and Tonkean macaques (Macaca tonkeana), bystanders are more likely to affiliate with one another to cope with social tension after fights (De Marco et al 2010;Judge and Mullen 2005). In several species, individuals use social grooming to reduce the tension generated when group members anticipate the competition induced by a forthcoming food distribution (Macaca arctoides: Mayagoitia et al 1993; Pan troglodytes: Koyama and Dunbar 1996; Cebus apella: Polizzi di Sorrentino et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Displacement activities appear when conflicting motivations are experienced simultaneously or when an animal is frustrated in performing a motivated action (Maestripieri et al, 1992). Displacement activities may present as a wide range of actions including licking, yawning, chewing and mouth twisting (Baker and Aureli, 1997;De Marco et al, 2010;Vick and Paukner, 2010;Mohiyeddinin and Semple, 2013). Displacement yawning is broadly recognized to increase with anxiety or social conflict in primates (e.g., Macaca nigra, Hadidian, 1980;M.…”
Section: Can Facial Expression Indicate Negative Affective States?mentioning
confidence: 99%
“…Pain will be examined in a separate section due to its specific, well-defined contribution to poor welfare states, as well as the comparatively large body of literature on facial indicators of pain. In mammals, facial expressions have been extensively Cabanac and Lafrance, 1990Spotila et al, 1977Wells, 1978;Robertshaw, 2006Gaughwin, 1979Stahlbaum and Houpt, 1989;Weeks et al, 2002;Charpentier et al, 2013Fox, 1970Sandem and Braastad, 2005;Kaiser et al, 2006;Bennett et al, 2012 Sefcek andKing, 2007;Knierim et al, 2007Partan, 2002Parr et al, 2005Parr et al, , 2007Bethell et al, 2012 Baker andAureli, 1997;Sandem et al, 2002;De Marco et al, 2010;Vick and Paukner, 2010Nagasawa et al, 2013Redbo, 1998Mason et al, 2007;Fernandez et al, 2008;Mason, 2010;Fureix et al, 2011;Tan et al, 2013Fox, 1970Waller and Dunbar, 2005;Judge and Bachmann, 2013;Yanagi andBerman, 2014 Craig et al, 1991;Langford et al, 2010;Sotocinal et al, 2011;Leach et al, 2012;Dalla Costa et al, 2014;Wathan et al, 2015;McLennan et al, 2...…”
mentioning
confidence: 99%
“…They show great propensity for appeasement and reconciliation of group members after conflict (Demaria and Thierry, 2001;Thierry et al, 2008). They are also characterized by complex polyadic interactions; when conflicts occur third parties can stop aggression by addressing appeasement signals to adversaries , and groupmates uninvolved in a conflict are more likely to affiliate with one another after witnessing it (De Marco et al, 2010).…”
mentioning
confidence: 99%